Mastering the Nikon COOLPIX A - Young, Darrell, 1958- (Rocky Nook, Inc., 2014)
This ebook explores the features and capabilities of the camera in a way that far surpasses the user's manual. It includes an in-depth look at the camera's controls and functions. It guides readers through the camera features with step-by-step setting adjustments; color illustrations; and detailed explanations for each option. Every button, dial, and menu configuration setting is explored in a user-friendly manner, with suggestions for setup according to various shooting styles.